2019
DOI: 10.3390/ijerph16244974
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Responses to Various 1 × 1 Small-Sided Games in Youth Soccer Players

Abstract: The aim of this study was to determine relationships between repeated 1 × 1 small-sided games (SSGs) (variable duration, constant work-to-rest ratio) and the concentration of steroid hormones and characteristic fatigue markers in youth soccer players. Eighteen young male soccer players were assigned at random to two experimental groups: E1—undertaking a six 30 s one-on-one SSGs with a 2 min rest period; and E2—playing six 45 s SSGs with a 3 min rest interval. Capillary blood was collected from the players at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Cortisol is considered to be a catabolic hormone because it stimulates glycogenolysis in the liver by increasing the glucose concentration in blood. It inhibits muscle uptake of amino acids and limits muscle protein synthesis [ 15 , 16 ]. Testosterone via its anabolic impact on the body causes the increase in the synthesis of muscle tissue, forming mass and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol is considered to be a catabolic hormone because it stimulates glycogenolysis in the liver by increasing the glucose concentration in blood. It inhibits muscle uptake of amino acids and limits muscle protein synthesis [ 15 , 16 ]. Testosterone via its anabolic impact on the body causes the increase in the synthesis of muscle tissue, forming mass and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…At rest, only 1% of testosterone circulates in the blood in the free form (FT) and is metabolically active. The remaining part is linked to the sex hormone-binding globulin (SHBG) and with albumins [ 16 , 17 ]. Analysis of the testosterone/cortisol T/C ratio is not only a good indicator of the body’s metabolic balance but is also found in the literature to be an indicator of peripheral and central fatigue in athletes [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity exercise has been known to increase circulating IGF-1, one of the most important anabolic factors, that takes place following exercise below and above the anabolic threshold ( Copeland and Heggie, 2008 ; Żebrowska et al, 2009 ; Hackney et al, 2016 ). Exercise-associated increase in testosterone (T) and T/C ratio, might potentially influence muscle protein synthesis, anti-inflammatory properties, and GH/IGF-1 axis response to exercise ( Chmura et al, 2019 , Oliveira et al, 2009). It has been hypothesized that testosterone induced a reduction in circulating IGF-1 levels and may have a direct, IGF-1 and GH-independent effect on muscle growth.…”
Section: Introductionmentioning
confidence: 99%
“…There are a limited number of published studies on the acute neuromuscular, biochemical, or endocrine responses to soccer training. Chmura et al (2019) examined T and C concentrations in response to a 1 vs 1 SSG with variable durations but constant work-to-rest ratios (i.e., 1:4).…”
Section: Acute Responses To Soccer Trainingmentioning
confidence: 99%
“…Despite the fatigue and recovery time course from matches being studied extensively (e.g., Nedelec et al, 2012;Silva et al, 2018), there is very limited research on the impact of SSG training on fatigue and recovery markers, which may have important implications for their placement within the training week. To date, the only study that has assessed the acute hormonal responses to isolated SSG training was performed by Chmura et al (2019), however, they only studied the T and C responses to 1 vs 1 SSG training up to 30-min post-exercise. The authors concluded that a longer recovery time between SSG repetitions reduced the immediate catabolic response in this cohort of u-18 soccer players.…”
Section: Summary Of the Previous Responses To Trainingmentioning
confidence: 99%